2012
DOI: 10.1016/j.jpain.2012.09.006
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analytic Review of the Hypoalgesic Effects of Exercise

Abstract: The purpose of this article was to examine the effects of acute exercise on pain perception in healthy adults and adults with chronic pain using meta-analytic techniques. Specifically, studies using a repeated measures design to examine the effect of acute isometric, aerobic, or dynamic resistance exercise on pain threshold and pain intensity measures were included in this metaanalysis. The results suggest that all three types of exercise reduce perception of experimentally induced pain in healthy participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
584
10
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 487 publications
(630 citation statements)
references
References 68 publications
25
584
10
11
Order By: Relevance
“…aerobic, isometric, and resisting exercises resulted in pain alleviation in healthy adults, as well as in some people with chronic pain [24]. Physical activity may have a beneficial influence on pain alleviation by increasing the pain threshold as a result of exercise-induced hypoalgesia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…aerobic, isometric, and resisting exercises resulted in pain alleviation in healthy adults, as well as in some people with chronic pain [24]. Physical activity may have a beneficial influence on pain alleviation by increasing the pain threshold as a result of exercise-induced hypoalgesia.…”
Section: Resultsmentioning
confidence: 99%
“…Physical activity may have a beneficial influence on pain alleviation by increasing the pain threshold as a result of exercise-induced hypoalgesia. the influence of the serotonin and adrenergic downward systems, as well as the effect of endogenous opioids and cannabinoids, has also been considered here [24,25]. the type, length, and intensity of physical effort influence the nature of posteffort hypoalgesia.…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis assessing pain responses following a single exercise session concluded that effects sizes were highly variable for individuals with chronic pain; although moderate/high-intensity exercise may exacerbate pain for individuals with widespread chronic pain. 10 Similarly, we have shown that women with fibromyalgia experience variability in their pain response (ie, increase, decrease, and no change in pain) following isometric contractions held to exhaustion. 11 In the current adolescent study, pain relief was assessed following a single exercise session only.…”
mentioning
confidence: 78%
“…Finally, for individuals with a regional pain condition, exercise is an excellent option because of its systemic effects; exercising a distal muscle can produce EIH at the painful muscle. 10 We look forward to continuing this discussion and exploring the best way to use exercise and CPM in pediatric physical therapy. …”
mentioning
confidence: 99%
“…There is a long history of studying the effects of exercise on pain perception (for review see [1,2,3]). Exercise can reduce the perception of pain-eliciting mechanical, thermal, and electrical stimuli [4,5,6,7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%